Innovation and technological development of industrial regions in the conditions of socio-economic insecurity - Golova, Irina Markovna; Sukhovey, Alla Filippovna (Economy of Regions, 2015)
The article is devoted to the identification of the characteristics and priorities of innovation and technological development in the industrial regions of the Russian Federation in the context of the ongoing global crisis. The authors come from the hypothesis that, in these circumstances, the strategy of innovative development of industrial regions, in order to ensure their sustainability and the creation of conditions for further growth, should be an integral part of their industrial policies and focus primarily on the modernization and improvement of technical and technological level of basic units. On the basis of the analysis of statistical data about the status of the innovation capacity in the Russian Federation, the authors have identified the root causes of the continuing backlog of advanced foreign countries by the level of innovative development (raw-material orientation of the Russian economy that enhances the technological dependence of the developed countries; insufficient financial support for innovation activities by the state; the orientation of innovation in imitation and borrowing). The necessity to take into account in the development and implementation of the socio-economic strategic regions of the Russian Federation and the close relationship between the industrial-technological and innovation component of social development is proved. In order to improve the effectiveness of regional development policies, the classification of Russian regions considering their industrial and technological specialization is proposed, the required elements and characteristics of effective innovation systems for each type of region are allocated. In the article, the proposals on measures of the state support for innovation development of industrial regions, with the aim of improving their sustainability and competitiveness in the face of geopolitical and economic uncertainty are determined. The article is addressed to professionals in the field of theory and practice in the management of innovative processes.